South Pole Ice Core (SPICEcore) SPC14 Core Quality Versus Depth - Aydin, Murat; Casey, Kimberly A.; Fegyveresi, John M.; Fudge, T. J.; Hargreaves, Geoff; Kahle, Emma; Nicewonger, Melinda R.; Nunn, Richard; Souney, Joseph Jr.; Steig, Eric J.; Twickler, Mark (IEDA: US Antarctic Program Data Center, 2019)
Abstract: Qualitative assessment of ice-core quality versus depth for the South Pole ice core SPC14. The depths and core quality ratings presented here are from the field observations made at South Pole, Antarctica, during the course of the drilling of the ice core and also from the lab observations at the NSF-Ice Core Facility in Lakewood, Colorado. Depths are in meters. Core quality ratings were defined are as follows. Excellent: 0–1 breaks/no fractures; Very Good: 0–2 breaks/90% no fractures; Good: 0–3 breaks/50% no fractures; Fair: >10 cm without fractures; Poor: >10 cm without through fractures; Very Poor: <10 cm without through fractures.